A Development of an Induction Heating Process for a Jewelry Factory: Experiments and Multiphysics - Thodsaphon Jansaengsuk; Sorathorn Pattanapichai; Jatuporn Thongsri (My University, 2023)
This article reports a successful development of the induction heating process (IHP) in a jewelry factory based on experiments and multiphysics consisting of electromagnetic and thermal simulations. First, two experiments were set to measure essential parameters for result validation and multiphysics boundary condition settings. Then, the essential parameters were applied to multiphysics, and both simulation results revealed heat transfer, magnetic flux density (B) generated by the coil, and temperature (T) of the product. B and T were consistent with the experimental results and theory, confirming the reliability of the multiphysics and methodology. After that, all simulation results were analyzed to assess and optimize IHP in terms of the number of coil turns (N), positional placement of the product (P), and coil thickness (Th). Multiphysics revealed that the current operating condition with N = 3 is proper; however, the IHP can be improved more with coil and operating condition optimizations. Finally, completing the optimizations, decreasing 40% of Th with N = 6, and the same P, increased B on the product by 21.62%, leading to IHP efficacy enhancement. The research findings are the optimum coil model and methodology for developing the IHP, which were practically employed in the jewelry factory.
Keywords: Multiphysics; Factory (object-oriented programming); Induction Heating; Induction Heating and Inverter Technology